Retinoblastoma - Rares, Laya (e-CliniC, 2016)
Abstract: Retinoblastoma is a malignant intraocular neuroblastic tumor that occurs at childhood, and has a hereditary property in around 40% of cases. The most common symptoms are leukocoria (50-62%), strabismus (20%), spontaneous hyphema, and amaurotic catâ€™ eye. Diagnosis is based on X ray examination, USG, CT Scan or MRI, and LDH, however, genetic counseling is also needed. The classification system commonly used for intraocular retinoblastoma is Reese-Ellsworth classification. Retinoblastoma therapy has to be performed at the time of confirmed diagnosis. However, there is a controversy whether surgey or chemotherapy will come first because both have their own advantages and disadvantages. The prognosis of children with localized intraocular retinoblastoma treated with modern therapy is good and the survival rate is more than 95%. Around 90% of children can survive more than 5 years after the diagnosis of retinoblastoma Keywords: retinoblastoma, leukocoria, strabismus, holistic management Â Abstrak: Retinoblastoma merupakan tumor neuroblastik intraokuler ganas, terjadi pada masa anak-anak, bersifat herditer (40%). Gejala yang paling sering adalah leukokoria (50-62%), strabismus (20%), hifema spontan, dan amaurotic catâ€™ eye. Diagnosis ditegakkan berdasarkan pemeriksaan X foto, USG, CT Scan atau MRI, dan LDH. Konseling genetik juga diperlukan dalam pemeriksaan pasien retinoblastoma. Sistem klasifikasi yang sering digunakan pada retinoblastoma intraokular ialah klasifikasi Reese-Ellsworth. Terapi retinoblastoma harus dilakukan saat anak terdiagnosis. Yang menjadi kontroversi apakah dilakukan pembedahan atau kemoterapi terlebih dahulu karena masing-masing tindakan ini mempunyai efek menguntungkan dan merugikan. Anak-anak dengan retinoblastoma intraokular terlokalisasi yang mendapatkan terapi modern mempunyai prognosis yang baik untuk bertahan hidup dengan persentase melebihi 95%. Sekitar 90% anak-anak dapat bertahan lebih dari 5 tahun setelah terdiagnosis retinoblastoma. Kata kunci: retinoblastoma, leukokoria, strabismus, penanganan holistik